(3GdYhdeI hbVGjGfG (B/s - (3GdSYOhf, MejO MeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2000)
(3GdYhdeI hGdOhd GdfGejI,GdYhdeI hGdOhdI GdbhejI,GdYhdeI hGdYQH,GdYhdeI hGdghjI GdKbGajI GdbhejI,GdYhdeI GdeSdMI hYhdeI GdSdGMs
(3HHdjhZQGajG(B:(3U(B.79-82s
Keywords: (3GdYhdeIs